2017
DOI: 10.1080/1120009x.2017.1338845
|View full text |Cite
|
Sign up to set email alerts
|

News on therapeutic management of MDR-tuberculosis: a literature review

Abstract: In 2015, the World Health Organization registered 10.4 million people who developed tuberculosis worldwide and 480,000 new cases of multidrug-resistant tuberculosis were identified. The care of multi and extensively drug-resistant tuberculosis is based on a combination of pyrazinamide and second-line drugs. These regimens are lengthy, partially effective and poorly tolerated. The challenge is to re-evaluate the use of existing molecules and to develop new agents more effective against resistant strains with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…Despite these analogues displaying enhanced antimycobacterial activity in vitro and in vivo, levofloxacin was shown to be more cost-effective, and therefore more accessible in resource-limited high burden settings [18]. In comparison to moxifloxacin, gatifloxacin and levofloxacin, DC-159a, a relatively new fluoroquinolone analogue was shown to exhibit enhanced bactericidal activity against MDR-TB both in vitro and in vivo and may therefore be a promising new therapeutic candidate for reducing treatment time for both MDR-and drug-sensitive (DS)-TB [22,23].…”
Section: Moxifloxacin Gatifloxacin Levofloxacin and Dc-159amentioning
confidence: 99%
“…Despite these analogues displaying enhanced antimycobacterial activity in vitro and in vivo, levofloxacin was shown to be more cost-effective, and therefore more accessible in resource-limited high burden settings [18]. In comparison to moxifloxacin, gatifloxacin and levofloxacin, DC-159a, a relatively new fluoroquinolone analogue was shown to exhibit enhanced bactericidal activity against MDR-TB both in vitro and in vivo and may therefore be a promising new therapeutic candidate for reducing treatment time for both MDR-and drug-sensitive (DS)-TB [22,23].…”
Section: Moxifloxacin Gatifloxacin Levofloxacin and Dc-159amentioning
confidence: 99%
“…In 2020, the World Health Organization estimated that about 10 million people (range: 8.9–11.0 million) contracted tuberculosis (TB) in 2019, which was responsible for 1.4 million deaths [ 1 ]. Treatment of drug-susceptible active tuberculosis consists of a standard 6-month regimen of four antimicrobials (usually isoniazid, rifampin, pyrazinamide, and ethambutol) [ 2 , 3 ]. However, these regimens are lengthy, only partially effective, and associated with high rates of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, new generation of quinolone derivative, TBK 613, has also shown promising antitubercular activity (Spigelman, 2008) with possible efficacy against fluoroquinolone-resistant strains (Maitra et al, 2015). Another molecule of quinolone family, DC-159a, was DNA gyrase A inhibitor that demonstrated dose-dependent bactericidal activity and MIC 90 was found to be 8 times lower than MFX (moxifloxacin) (Barthod et al, 2017). Bogatcheva et al (2011) reported the identification of SQ609 as a lead compound from a library of dipiperidines.…”
Section: Introductionmentioning
confidence: 99%